Pengaruh Star Seller dan Online Customer Riview Terhadap Kepercayaan Konsumen (Studi Kasus: Pengguna Shopee di Kecamatan Medan Petisah) - Wafiq, Wafiqotul Azizah; Wan Rizca Amelia (Jurnal Bisnis Administrasi dan Manajemen, 2025)
The purpose of this research is to find out the influence of Star Seller on consumer trust, to find out the influence of Online Customer Reviews on consumer trust and to find out the effect of Star Seller and Online Customer Reviews on consumer trust (Case study of Shopee users in Medan Petisah District). The population in this study was the community in Medan Petisah District, totaling 72,432 people. The sample in the study was 100 people taken using the Slovin formula. The data collection technique used in this research was carried out by distributing questionnaires. The analysis techniques used in this research are multiple linear regression, partial test (t test), simultaneous significance test (F test) and coefficient of determination. The research results show that there is a positive and significant influence of star sellers on consumer trust, there is a positive and significant influence of online customer reviews on consumer trust and star sellers and online customer reviews have a positive and significant influence on consumer confidence of Shopee users in Medan Petisah District. Keywords: Star Seller, Online Customer Review and Consumer Trust. The purpose of this research is to find out the influence of Star Seller on consumer trust, to find out the influence of Online Customer Reviews on consumer trust and to find out the effect of Star Seller and Online Customer Reviews on consumer trust (Case study of Shopee users in Medan Petisah District). The population in this study was the community in Medan Petisah District, totaling 72,432 people. The sample in the study was 100 people taken using the Slovin formula. The data collection technique used in this research was carried out by distributing questionnaires. The analysis techniques used in this research are multiple linear regression, partial test (t test), simultaneous significance test (F test) and coefficient of determination. The research results show that there is a positive and significant influence of star sellers on consumer trust, there is a positive and significant influence of online customer reviews on consumer trust and star sellers and online customer reviews have a positive and significant influence on consumer confidence of Shopee users in Medan Petisah District. Keywords: Star Seller, Online Customer Review and Consumer Trust.